Myanmar Budget Brief, June 2022 - World Bank (Washington, DC, 2022)
This Budget brief presents a summary of developments in Myanmar's public finances. This report includes three sections that cover the aggregate fiscal update, a primer on public finance developments in core service ministries, and a longer-term view of fiscal management in Myanmar. The report relies on data obtained from published reports of the Ministry of Planning and Finance, open-source data, and news that was analyzed and cross-checked as part of the monitoring work. Where news reports are referenced, additional efforts were made during the monitoring process to triangulate reports from several reputed news media sources to ensure veracity of the information presented.